High Speed Data Converters - Ali, Ahmed M. A. (Materials, circuits and devices series ;, 2016)
High speed data converters represent one of the most challenging, important and exciting analog and mixed-signal systems. They are ubiquitous in our modern and highly connected world. Understanding and designing this class of converters require proficiency in analog circuit design, digital design, and signal processing. This book covers high speed data converters from the perspective of a leading high speed ADC designer and architect, and with a strong emphasis on high speed Nyquist A/D converters. Topics covered include an introduction to high-speed data conversion; performance metrics; data converter architectures; sampling; comparators; amplifiers; pipelined A/D converters; time-interleaved converters; digitally assisted converters; evolution and trends The book is intended for engineers and students who design, evaluate or use high speed data converters. A basic foundation in circuits, devices and signal processing is required. The book is meant to bridge the gap between analysis and design, theory and practice, circuits and systems. It covers basic analog circuits and digital signal processing algorithms. There is a healthy dose of theoretical analysis in this book, combined with the practical issues and intuitive perspectives.